Synthesis of nano-sized ZnO powders by thermal decomposition of zinc acetate using Broussonetia papyrifera (L.) Vent pulp as a dispersant - C. Liewhiran (2018)
Nano-sized ZnO powders were synthesized by thermal decomposition of zinc acetate and Broussonetia papyrifera (L.) Vent pulp. The pulp was soaked in zinc acetate solution for 24 h. The impregnated pulp was dried at 70 °C for 48 h. The mixture was calcined for 1 h at 600, 700, 800, and 900 °C. The reaction mechanisms to form the ZnO nanoparticles were evaluated using FT-IR spectroscopy. The calcined powders were characterized by XRD, SEM, and TEM. The values of surface area were calculated from BET data. The particle sizes of ZnO in the calcined powders ranged from 10 nm to 60 nm, and the surface area was 18.93 m2/g. © 2006 Elsevier B.V. All rights reserved.